Deep insights into the network of acetate metabolism in anaerobic digestion: focusing on syntrophic acetate oxidation and homoacetogenesis. (15th February 2021) - Pan, Xiaofang; Zhao, Lixin; Li, Chunxing; Angelidaki, Irini; Lv, Nan; Ning, Jing; Cai, Guanjing; Zhu, Gefu
Highlights: The generation and consumption network of acetate during AD was considered. The roles of syntrophic acetate oxidation and homoacetogenesis in AD were summarized. The metabolism pathways of SAO and homoacetogenesis were analyzed and compared. Energy conversion and interspecies electron transfer were reviewed. Abstract: Acetate is a pivotal intermediate product during anaerobic decomposition of organic matter. Its generation and consumption network is quite complex, which almost covers the most steps in anaerobic digestion (AD) process. Besides acidogenesis, acetogenesis and methanogenesis, syntrophic acetate oxidation (SAO) replaced acetoclastic methanogenesis to release the inhibition of AD at some special conditions, and the importance of considering homoacetogenesis had also been proved when analysing anaerobic fermentations. Syntrophic acetate-oxidizing bacteria (SAOB), with function of SAO, can survive under high temperature and ammonia/ volatile fatty acids (VFAs) concentrations, while, homoacetogens, performed homoacetogenesis, are more active under acidic, alkaline and low temperature (10°C-20°C) conditions, This review summarized the roles of SAO and homoacetogenesis in AD process, which contains the biochemical reactions, metabolism pathways, physiological characteristics and energy conservation of functional bacteria. The specific roles of these two processes in the subprocess of AD (i.e., acidogenesis, acetogenesis and methanogenesis) were also analyzed in detail. A two phases anaerobic digester is proposed for protein-rich waste(water) treatment by enhancing the functions of homoacetogens and SAOB compared to the traditional two-phases anaerobic digesters, in which the first phase is fermentation phase including acidogens and homoacetogens for acetate production, and second phase is a mixed culture coupling syntrophic fatty acids bacteria, SAOB and hydrogenotrophic methanogens for methane production. This review provides a new insight into the network on production and consumption of acetate in AD process. Graphical abstract: Image, graphical abstract